SOSIALISASI MENINGKATKAN PERAN PENASIHAT AKADEMIK KEPADA MAHASISWA ADMINISTRASI BISNIS UNIVRESITAS NEGERI MAKASSAR - Siti Syarifah Wafiqah Wardah; Muh. Rizal Suyuti; Yusi Irensi Seppa; Maya Kasmita; Fitriani Dzulfadhilah (Jurusan Teknik Informatika dan Komputer, 2023)
This community service activity is in the form of a socialization targeting Business Administration students at the Faculty of Social Sciences and Law, Makassar State University. The purpose of this service is to increase students' knowledge about the role of academic advisors and students' interest in conducting mentoring with their respective academic advisors. In addition, to provide understanding to students that mentoring activities with academic advisors are important activities within the university. The location of this service is carried out in one of the Business Administration Study Program classrooms and is also carried out online through the zoom application. The method used is by giving a lecture in the first session, then the second session of discussion with questions and answers, then the last session of evaluation. The results of this socialization activity increase the understanding of Business Administration students at Makassar State University regarding the role of academic advisors so that students will be active in meeting and communicating in terms of academic guidance or consultation.